Mobility and space use of moose in relation to spatial and temporal exposure to wolves - Balogh, Gyöngyvér (SLU/Dept. of Ecology, 2012)
In a predator-prey system, prey species may adapt to the presence of predators with behavioral changes such as increased vigilance, shifting habitats or changes in their mobility. Across North America, moose (Alces alces) have shown to adapt to their re-colonizing predators, the wolves (Canis lupus) but such anti-predator behavioral responses have not yet been found in Scandinavian moose. The more than a century long absence of wolves in Scandinavia and the current re-colonization since the 1980s provide unique conditions to further detail our knowledge of their effect on moose. I analyzed travel speed, linearity of movement and seasonal home range size of GPS collared female moose within the same moose population but with spatial (inside- / outside wolf territories) and temporal (before- / after the re-establishment of wolves) differences in the exposure to wolves. Differences in seasonal home range size of female moose in the study area correlated with exposure to wolves, as home ranges tended to be larger in areas of the wolf territory with a more frequent presence of wolves. Travel speed and linearity of movement were mostly affected by seasonal changes and differences in reproductive status. Travel speed was highest during the calving (May – Jul.) and postcalving (Aug. – Oct.) seasons, and was generally lower for females with calves than females without calves in all seasons. Related to presence of wolves, a generally suppressed travel speed was observed inside the wolf territory compared to outside, but an elevated mobility was seen in certain, more intensively used areas of the territory. The linearity of movement was mostly affected by reproduction, as more concentrated movement was observed at females with calves at heel, during the calving season. Overall, the results supported that mobility of female moose was more strongly influenced by external factors and reproductive status, than by the return of their long absent natural predators. This can be due to a combination of several factors including e.g. lower wolf densities, higher moose:wolf ratios and more intensive hunting harvest of the moose population than observed in North America.